2001
DOI: 10.1067/mtc.2001.112205
|View full text |Cite
|
Sign up to set email alerts
|

Operation for acute type A aortic dissection in octogenarians: Is it justified?

Abstract: Operations for acute type A dissection performed on octogenarians involve increased hospital mortality and morbidity. Short-term survival is unfavorable and is associated with a poor quality of life. Without additional corroborative studies to endorse the present findings, the use of age as a parameter to limit access of patients to expensive medical resources remains an unsubstantiated concept. In the context of acute type A aortic dissection, however, the hypothesis that older patients should be denied such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 7 publications
3
65
0
1
Order By: Relevance
“…102,103) With improved surgical outcomes, however, the issue has recently shifted to surgeries on AAAD patients over 80 years old. [104][105][106] Hata et al have devised "less invasive quick replacement (LIQR)" using distal anastomosis at a rectal temperature of 28 degrees without cerebral perfusion, followed by rapid warming with a heating mat and circulating blood at 40 degrees, achieving improved outcomes in elderly patients. 107) Rylski et al surveyed 381 septuagenarians and 83 octogenarians or older and reported that the former had acceptable mortality (30-day mortality of 16%) but the latter had higher mortality (35%).…”
Section: Age and Indication For Surgical Treatmentmentioning
confidence: 99%
“…102,103) With improved surgical outcomes, however, the issue has recently shifted to surgeries on AAAD patients over 80 years old. [104][105][106] Hata et al have devised "less invasive quick replacement (LIQR)" using distal anastomosis at a rectal temperature of 28 degrees without cerebral perfusion, followed by rapid warming with a heating mat and circulating blood at 40 degrees, achieving improved outcomes in elderly patients. 107) Rylski et al surveyed 381 septuagenarians and 83 octogenarians or older and reported that the former had acceptable mortality (30-day mortality of 16%) but the latter had higher mortality (35%).…”
Section: Age and Indication For Surgical Treatmentmentioning
confidence: 99%
“…46,157-161 The in-hospital mortality rate of acute type A dissection surgery has recently improved to about 10% in Japan. Listed risk factors for surgical death in patients with acute type A aortic dissection include advanced age (80 years or older), 162 preoperative shock, malperfusion of the vital organs, 163 preoperative brain damage, and massive bleeding during surgery.…”
Section: (3) Therapeutic Resultsmentioning
confidence: 99%
“…On the contrary, higher morbidity and mortality has been observed in high-risk combined procedures, 7) reoperations, 8) and acute aortic surgery. 9) Most of these studies examined postoperative outcome of distinct surgical procedures without special attention to overall perioperative risk. However, in our routine practice, we often assess octogenarians with many comorbidities, in whom the type of surgery constitutes only a part of the overall risk.…”
Section: Discussionmentioning
confidence: 99%